Localized Deformation of Lawsonite During Cold Subduction. Issue 2 (10th February 2022) - Shiraishi, R.; Muto, J.; Tsunoda, A.; Sawa, S.; Suzuki, A.
Abstract: One of the causes of intermediate depth (50–300 km) earthquakes in cold subduction zones is proposed to be the dehydration of lawsonite, a hydrous mineral that forms a major component of cold subducting oceanic crust. However, experimental studies are limited and the deformation mechanism of lawsonite remains uncertain. Here, we conducted deformation experiments on lawsonite under seismogenic conditions appropriate to cold subduction zones at pressures from 2.5 to 6.0 GPa and temperatures from 300°C to 800°C. Deformation experiments incorporating temperature ramping, in which deformation and heating were synchronous, did not show unstable fault slip associated with dehydration. Instead, we find localized deformation accompanying a rapid stress drop prior to the initiation of dehydration, and then more gradual strain weakening during dehydration. Such microstructures as microcracks and comminution of lawsonite imply a brittle behavior for lawsonite accompanied by the partial amorphization along the fault. Our results suggest that fault slip may occur within the stability field of lawsonite under conditions suitable for the generation of intermediate depth earthquakes. Plain Language Summary: An intermediate‐depth earthquake is one that occurs in a subducting plate at depths of between 50 and 300 km, and the causes of such earthquakes are debated. Although the embrittlement of hydrous minerals during dehydration is the most commonly accepted causal mechanism, based on high‐temperature, high‐pressure deformation experiments, we show that lawsonite, a major hydrous mineral in subduction environments, can exhibit localized deformation in the absence of dehydration. Microstructures indicate brittle behavior of lawsonite and localized deformation during cold subduction. Key Points: Sudden stress drops and strain localization occur within the stability field of lawsonite Microstructures of deformed lawsonite indicate brittle behavior under the conditions of cold subduction zones Localized deformation of lawsonite may be related to intermediate depth earthquakes